(untitled) (Annals of Medical Research, 2021)
Aim: Due to risk of severe bleeding of the organs and inveteracy acute immune thrombocytopenic purpura (ITP) is a disease that still preserves importance. In our region, cases of ITP retrospectively reviewed in terms of clinical characteristics and responses to the treatment options.